Perbandingan Suhu dan Kadar Leukosit Pada Pasien Appendisitis Akut dengan Pasien Appendisitis Perforasi - Mohd Reza Bahlia (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Late diagnosing appendicitis will increase the incidence of perforation of the appendix which causes dangerous complications. In diagnosing appendicitis, temperature assessment and leukocyte count can be carried out which is useful for indicating the presence or absence of an inflammatory/infectious reaction. This test is used to support the diagnosis of patients with acute appendicitis and perforated appendicitis. If the difference between the two patients is immediately known, this can be used as additional information in strengthening the diagnosis so that it can be determine the management quickly, precisely and increase awareness of complications. This study was conducted to compare the temperature and leukocyte levels of acute appendicitis patients with perforated appendicitis patients at Arun Lhokseumawe Hospital in 2019–2020. This study was an observational analytic study with a cross sectional approach. It was conducted on 45 patients with acute appendicitis and 45 patients with perforated appendicitis. The data were obtained from medical records and analyzed using the Mann Whitney test. The results showed that the average temperature of patients with acute appendicitis was 36,766 ± 0,083?C and patients with perforated appendicitis was 37,237 ± 0,146?C with p value = 0,040. The cut off point of temperature between acute appendicitis patients and perforated appendicitis patients was 37,8?C with sensitivity 22,22%, specificity 97,78% and AUC 62,3%. The average leukocyte level in patients with acute appendicitis was 9.989.67 ± 236,058 cells/mm3 and patients with perforated appendicitis was 16.808.89 ± 713,356 cells/mm3 with p value < 0,001. The cut off point of leukocytes between patients with acute appendicitis and patients with perforated appendicitis was 12,200 cells/mm3 with sensitivity 91,11%, specificity 88,89% and AUC 98,3%. The conclusion of the study stated that there were differences in body temperature values and blood leukocyte levels between patients with acute appendicitis and perforated appendicitis at Arun Lhokseumawe Hospital.